2002
DOI: 10.1034/j.1399-0039.2002.590601.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing vaccine design for cellular processing, MHC binding and TCR recognition

Abstract: In this review we describe the methods and processes that our group have developed while aiming to test and design multiepitope vaccines for infectious diseases and cancer. Testing the performance of vaccines composed of epitopes restricted by human leukocyte antigen (HLA) molecules is accomplished by in vitro antigenicity assays, as well as in vivo immunogenicity assays in HLA transgenics. The efficiency by which multiepitope vaccines are processed is optimized by spacer residues, which are designed to facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
86
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 42 publications
0
86
0
Order By: Relevance
“…Latter, the logical framework of this approach has been inverted. Instead of developing a single epitope for each of the common HLA alleles, attempts were made to identify epitopes capable of binding multiple HLA types (12)(13)(14)16). The grouping of alleles into supertypes, based on common structural and functional features, is useful in addressing such attempts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Latter, the logical framework of this approach has been inverted. Instead of developing a single epitope for each of the common HLA alleles, attempts were made to identify epitopes capable of binding multiple HLA types (12)(13)(14)16). The grouping of alleles into supertypes, based on common structural and functional features, is useful in addressing such attempts.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that certain class I alleles can recognize similar motifs (11)(12)(13)(14) and thus be grouped into HLA "supertypes", binding common "supermotifs". The classification of MHC molecules into supertypes, based on structural features and/or peptide specificity, is of prime importance in the development of epitope-based vaccines (15,16). The experimental determination of motifs for every allele is prohibitively expensive in terms of labor, time, and resources.…”
mentioning
confidence: 99%
“…can induce more potent immune responses and they appear to be safer to use and easier to produce [21,20,22,13].…”
Section: Introductionmentioning
confidence: 99%
“…E7-LLMGTLGIV82-90 was known to induce the cellular response in HLA A2.1 rabbit model [39] and reduced tumor burden in aged mice [40]. E6-KLPDLCTEL13-22 [41] and E7-TLQDIVLHL [7][8][9][10][11][12][13][14][15] One of the predicted peptides, QLFVTVVDT [42] were proved to be CTL epitopes for HPV 18.…”
Section: Discussionmentioning
confidence: 99%
“…The accurate identification of CTL epitopes is a critical step towards the development of peptide vaccine [12]. The identification of CTL epitopes could be accelerated using in silico prediction methods [13].…”
Section: Introductionmentioning
confidence: 99%